Alterations of Cardiac Protein Kinases in Cyclic Nucleotide-Dependent Signaling Pathways in Human Ischemic Heart Failure - Wang, Chunguang; Taskinen, Juuso H.; Segersvärd, Heli; Immonen, Katariina; Kosonen, Riikka; Tolva, Johanna M.; Mäyränpää, Mikko I.; Kovanen, Petri T.; Olkkonen, Vesa M.; Sinisalo, Juha; Laine, Mika; Tikkanen, Ilkka; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives Impaired protein kinase signaling is a hallmark of ischemic heart disease (IHD). Inadequate understanding of the pathological machanisms limits the development of therapeutic approaches. We aimed to identify the key cardiac kinases and signaling pathways in IHD patients with an effort to discover potential therapeutic strategies. Methods Cardiac kinase activity in IHD left ventricle (LV) and the related signaling pathways were investigated by kinomics, transcriptomics, proteomics, and integrated multi-omics approach. Results Protein kinase A (PKA) and protein kinase G (PKG) ranked on top in the activity shift among the cardiac kinases. In the IHD LVs, PKA activity decreased markedly compared to that of controls (62% reduction, p=0.0034) whereas PKG activity remained stable although the amount of PKG protein increased remarkably (65%, p=0.003). mRNA levels of adenylate cyclases (ADCY 1, 3, 5, 9) and cAMP-hydrolysing phosphodiesterases (PDE4A, PDE4D) decreased significantly, while no statistically significant alterations were observed in that of PKGs (PRKG1 and PRKG2) and guanylate cyclases (GUCYs). The gene expression of natriuretic peptide CNP decreased remarkably whereas those of BNP, ANP, and nyprilysin increased significantly in the IHD LVs. Proteomics analysis revealed a significant reduction in protein levels of ‘Energy metabolism’ and ‘Muscle contraction’ in the patients. Multi-omics integration highlighted intracellular signaling by second messengers as the top enriched Reactome pathway. Conclusions The deficiency in cAMP/PKA and cGMP/PKG signaling pathways is strongly implicated in the pathogenesis of IHD. Natriuretic peptide CNP could be an attractive therapeutic target for the modulation of cGMP/PKG signaling.